Comparasi Edge Detection Roberts dan Morfologi Pada Deteksi Plat Nomor Kendaraan Roda Dua - Dedy Abdullah; Erwin Dwika Putra (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2018)
Refers to the difficulty factor on the detection plate on this research will focus on the detection of two-wheeled vehicle number plate, where the data will be taken from the farm garage. The resolution of this problem will be attempted using techniques of digital image processing method of detection of edge (edge detection) and morphology. Study on the evaluation and the research results will be calculated using the technique of confussion matrix, this technique will measure on the success rate of approach will be obtained from the proposed method. of the proposed method is sufficiently high, namely 53% success rate, while the value of positive predictive value by which this value to know the success rate of the method to detect the entire image test is still extremely less just reached 40% success, while the value of negative value which is the value of preditive to know separation detection noise his success pretty well with a value of 56% success rate Keyword: Edge Detection, Morfologi, Confusion Matrix